Creating Student Discipline Character Through Pandu Hidayatullah Movement at Tahfidz Ar-Rahmah Malang Senior High School - Fadhilah, Hanif; Umiarso, Umiarso; Yusuf , Muhammad (Mudir : Jurnal Manajemen Pendidikan, 2023)
Pondok SMA Tahfidz Ar-Rohmah Malang which is known as an Islamic educational institution in promoting memorization of the Qur'an, allows many administrators to participate in building the success of the character of students. The management of students in this cottage is certainly not spared in helping, supervising, and carrying out activities that take place at every event, then there is an important role of the Hidayatullah Pandu movement in the formation of the character of students in the Pondok SMA Tahfidz Ar-Rohmah Malang. In this study, researchers used qualitative methods with a qualitative approach. This approach focuses on observation, in-depth interviews, shooting and recording. The purpose of this study was to determine the formation of disciplinary character through GPH. This study provides knowledge of the success of the management of GPH in the formation of the character of students from the discipline of each student.The results showed that Hidayatullah Pandu movement has significant potential in shaping the character of discipline in learners. Through activities such as discipline training, understanding life values, and participation in social activities, learners can develop disciplined mindsets, attitudes, and behaviors. From every event that takes place in the cottage, GPH always plays an important role to help, supervise and carry out the activities carried out.